Patent Boxes Design, Patents Location and Local R&D - Annette Alstadsæter; Salvador Barrios; Gaëtan J. A. Nicodème; Agnieszka Skonieczna; Antonio Vezzani (Center for Economic Studies and ifo Institute (CESifo), 2015)
Patent boxes have been heavily debated for their role in corporate tax competition. This paper uses firm-level data for the period 2000-2011 for the top 2,000 corporate research and development (R&D) investors worldwide to consider the determinants of patent registration across a large sample of countries. Importantly, we disentangle the effects of corporate income taxation from the tax advantage of patent boxes. We also exploit a new and original dataset on patent box features such as the conditionality on performing research in the country, and their scope. We find that patent boxes have a considerable effect on attracting patents, mostly because of their favourable tax treatment, especially for high-quality patents. Patent boxes with a large scope in terms of tax base definition also have stronger effects on the location of patents. The size of the tax advantage offered through patent box regimes is found to deter local innovative activities, whereas R&D development conditions tend to attenuate this adverse effect. Our simulations show that, on average, countries imposing such development conditions tend to grant a tax advantage that is slightly greater than optimal from a local R&D impact perspective.
Keywords: F21; F23; H25; H73; O31; O34; 330; corporate taxation; patent boxes; location; patents; R&D; nexus approach